Theoretical and experimental research on the influence of initial temperature on the flammability of hydrocarbon-CO2 mixture using in organic Rankine cycle. (15th January 2019) - Tian, Hua; Liu, Yuewei; Shu, Gequn; Li, Linqing; Huo, Xu
Abstract: As an effective waste heat recovery technique, the hydrocarbon-CO2 mixture based Rankine cycle is always operating on a specific temperature, which has a noticeable influence on flammability limits. Thus it is critical to research flammability limit of hydrocarbon-CO2 at various initial temperatures. Focusing on the hydrocarbon-CO2 mixture, this paper first measured its flammability limits at different initial temperatures using an experimental setup based on the ASTM E681-09. Results have shown that lower flammability limit decreases with the elevating initial temperatures while upper flammability limit increases, therefore the flammable zone expands leading to higher potential dangers. Moreover the expansion values of flammable zone from 30 °C to 70 °C have decreased by nearly 0.3  vol% with the dilute concentration changing from 0 to 0.9. A linear relationship between temperature and flammability limits of hydrocarbon-CO2 mixture has been proposed based on thermal theory and verified with experimental values. At the same time, a comprehensive method based on calculated adiabatic flame temperature theory was presented to predict the flammability limit at different temperatures with higher accuracy. The mean relative deviation between the predicted results and observed ones is 2.76% at upper flammability limit and 1.71% at lower flammability limit in the temperature range examined. Highlights: Flammability limits were measured experimentally at various initial temperatures. The effects of both initial temperature and dilute concentration are conducted. A prediction model based on adiabatic flame temperature has been proposed. The improved accuracy has been acquired in this prediction model.